The Relationship between Use of 3-Month Injectable Family Planning for Family Planning Acceptors and Menstrual Patterns in the Working Area of the Barong Tongkok Health Center, West Kutai Regency in 2022 - Marhamah; Joko Sapto Pramono; Nilam Noorma (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the relationship between the use of 3-month injectable family planning in family planning acceptors and menstrual patterns in the working area of ​​the Barong Tongkok Health Center, West Kutai Regency. This type of research is correlational with a cross sectional approach. The population in this study were all 3-month injection family planning acceptors at the Barong Tongkok Health Center, namely 76 acceptors per month. Sampling in this study using accidental sampling technique and obtained as many as 44 respondents. Data collection was carried out by interviewing and using a questionnaire. The data analysis technique uses univariate analysis to determine the frequency distribution of variables and bivariate analysis uses the chi square test to determine the relationship between variables. The results of the hypothesis test obtained a p-value of 0.024 (<0.05), so it can be concluded that there is a relationship between the use of 3-month injections in family planning acceptors and menstrual patterns in the working area of ​​the Barong Tongkok Health Center, West Kutai Regency.